A challenging diagnosis of malignant mesothelioma with osteosarcomatous differentiation metastasizing to bone. Issue 8 (19th September 2020) - Brown, Michael; Jersmann, Hubertus; Crowhurst, Thomas; Van Vliet, Chris; Crouch, Gareth; Badiei, Arash
Abstract: Malignant pleural mesothelioma (MPM) is an insidious primary neoplasm of the pleura that can be challenging to diagnose and is commonly considered to be only locally invasive. We present the case of a 74‐year‐old male who presented with clinical features of MPM but from whom pleural fluid and biopsies initially suggested benign pathology. He later developed diffuse bony metastases and re‐examination of pleural biopsies using modern immunohistochemistry and molecular testing revealed a diagnosis of sarcomatoid and desmoplastic MPM with heterologous osteosarcomatous differentiation. This case not only demonstrates the rare potential of skeletal metastasis of MPM, but also highlights the importance of recognizing the utility of modern diagnostic tests and their potential to prevent the need for unnecessary invasive procedures. To our knowledge this is the first description of this rare histological sub‐type presenting with skeletal metastases. Abstract : We present a case of bony metastasis from a rare histological subgroup of malignant pleural mesothelioma. The diagnosis was challenging; however, modern immunohistochemistry and molecular testing provided a diagnostic opportunity and potentially saved further unnecessary investigation.